Kuat Lentur Balok Laminasi Kayu Mangga Berbasis Defeleksi dan Regangan dengan Sistem Pembebanan Four Point Bending - Baide, H.O.; Siregar, A.P.N. (Tadulako University, 2024)
To meet the standard needs of low-quality wood structures, special methods are needed that can meet these needs. So the shape of the structure was developed, not whole wood but laminated components made through gluing or commonly called laminated beams This study aims to determine the difference between laminated beams and solid blocks of mango wood through testing the bending strength of beams. The research method used in this study uses quantitative methods with an experimental method approach. The research conducted used Mango wood samples with two types of block treatment, namely laminated beams and solid blocks. The laminated beam is made using 5 layers of Mango wood with a size after lamination of 1200 x 100 x 50 mm. As for solid beams using a size of 1200 x 100 x 50 mm. Then the wood is tested by applying two centralized loads on two pedestals at a distance of 30 cm from the pedestal. The results showed that from testing mechanical properties which in this case is limited only by flexural strength testing. The flexural strength test in question is four point bending. The results of the flexural strength test obtained an average value of modulus of elasticity (MOE) of laminated beams of 6804.796 MPa while for solid beams of 9130.465 MPa. According to SNI 7973-2013. The average value of bending strength (MOE) was obtained 6804.796 MPa for laminated wood and 9130.465 MPa for solid wood. According to SNI 7973-2013, the value of laminated wood in this study is included in the E13 quality code. As for solid wood, it is included in the E18 quality code. This shows that the MOE value of solid beams is greater than the MOE of laminated beams. Then in the modulus of rapture (MOR) test, the average MOR value of laminated beams was 66.205 MPa and solid beams of 95.007 MPa. This shows that the MOR value of laminated beams is smaller than the MOR value of solid beams.